Environmental security in transnational contexts what relevance for regional human security regimes? - Koff, Harlan; Maganda, Carmen (Rethinking globalizations, 2018)
This book contends that human and environmental security should be framed in terms of transnational discussions rather than being limited to general international debates in order to examine both governance challenges and potential policy mechanisms that can effectively address environmental security issues that cross national boundaries. The chapters in this volume undertake an empirical examination of the relationships between human and environmental security, cross-border exchanges, and regional integration.